2020
DOI: 10.1002/mds.28260
|View full text |Cite
|
Sign up to set email alerts
|

Four‐Year Follow‐up of [18F]Fluorodeoxyglucose Positron Emission Tomography–Based Parkinson's Disease–Related Pattern Expression in 20 Patients with Isolated Rapid Eye Movement Sleep Behavior Disorder Shows Prodromal Progression

Abstract: Background Isolated rapid eye movement sleep behavior disorder is known to be prodromal for alpha‐synucleinopathies, such as Parkinson's disease (PD) and dementia with Lewy bodies. The [18F]fluorodeoxyglucose‐positron emission tomography (PET)–based PD‐related brain pattern can be used to monitor disease progression. Objective We longitudinally investigated PD‐related brain pattern expression changes in 20 subjects with isolated rapid eye movement sleep behavior disorder to investigate whether this may be a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 26 publications
(52 reference statements)
4
36
0
Order By: Relevance
“…There was a trend toward elevated PDRP expression in the converters than in the nonconverters, which is grossly similar to a prior study by Holtbernd et al 17 More importantly, most PD converters showed the increased PDRP expression along with the decreased RBDRP expression, and this tendency was not observed in patients who developed DLB or MSA. The PDRP expression in our PD converters are in line with a recent longitudinal study by Kogan et al 27 who reported that all 4 iRBD patients who developed PD had suprathreshold PDRP expression at baseline and its greater increase over approximately 4 years of follow‐up. Given the current results, one could speculate that the RBDRP tends to fade away, being replaced by the disease‐specific pattern of the phenoconversion diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…There was a trend toward elevated PDRP expression in the converters than in the nonconverters, which is grossly similar to a prior study by Holtbernd et al 17 More importantly, most PD converters showed the increased PDRP expression along with the decreased RBDRP expression, and this tendency was not observed in patients who developed DLB or MSA. The PDRP expression in our PD converters are in line with a recent longitudinal study by Kogan et al 27 who reported that all 4 iRBD patients who developed PD had suprathreshold PDRP expression at baseline and its greater increase over approximately 4 years of follow‐up. Given the current results, one could speculate that the RBDRP tends to fade away, being replaced by the disease‐specific pattern of the phenoconversion diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…However, in contrast to the clinical score of the signature, which requires 16 variables in order to yield one patient‐specific clinical score (including the first 3 parts of the UPDRS, 3 different quantitative motor tasks, an extensive neuropsychological with enough cognitive tasks to generate composite scores for the attention and executive functions, episodic memory and learning, and visuospatial domains), the MRI signature has the advantage of only requiring a single anatomic T1‐weighted MRI scan. Several imaging markers have been proposed to identify patients with PD at higher risk of cognitive decline; 63–67 however, they often involved modalities and analytical procedures that are costly, highly technical, or hard to access. There is therefore a need for a more cost‐efficient brain marker that could be implemented in large clinical trials, especially in order to select patients that would be more likely to evolve toward a phenotype in which cognition becomes significantly affected.…”
Section: Discussionmentioning
confidence: 99%
“…All but one [33] of the included articles investigated global cognition (13,171 Five studies employed data suitable for meta-analysis on screening tests (MoCA or versions of the MMSE) for incident PD, varying between 0.61 and 1.92, with a pooled estimate of 1.08 (95% CI 0.66-1.77, Figure 3A).…”
Section: Global Cognition: Screening Testsmentioning
confidence: 99%